Simplified cascade multiphase DC-DC buck power converter for low voltage large current applications: part I — steady-state analysis - Anand Bannet Ganesen; Nungky Prameswari; Falah Kharisma Nuraziz; Arwindra Rizqiawan; Pekik Argo Dahono (Institute of Advanced Engineering and Science, 2021)
This paper presents a new simplified cascade multiphase DC-DC buck power converter suitable for low voltage and large current applications. Cascade connection enables very low voltage ratio without using very small duty cycles nor transformers. Large current with very low ripple content is achieved by using the multiphase technique. The proposed converter needs smaller number of components compared to conventional cascade multiphase DC-DC buck power converters. This paper also presents useful analysis of the proposed DC-DC buck power converter with a method to optimize the phase and cascade number. Simulation and experimental results are included to verify the basic performance of the proposed DC-DC buck power converter.